Método de estabilização submalha difusão dinâmica aplicado na simulação de escoamentos miscíveis em meios porosos - Werner, Suzi Lara (2011)
This work presents a finite element formulation to solve a coupled non-linear system of partial differential equations, composed by an elliptic sub-system for the pressure-velocity and an advective-diffusive transport equation for the concentration for miscible displacements in porous media. The pressure is determined by the classical Galerkin method and it is considered a post-processing technique for the velocity field. The Dynamic Diffusion subgrid stabilization method is used in the concentration equation. This method is based on the multiscale formalism and consist to add in the classical Galerkin formulation enriched with bubbles functions a nonlinear and non parameterized dissipative operator acting isotropically in all discretization scales. The resulting nonlinear system of ordinary differential equations are discretized using the implicit predictor/multicorrector scheme. Numerical simulations of tracer injection processes and miscible displacements with high adverse mobility ratios in two dimensions are reported, and comparisons with the SUPG/CAU stabilized formulation are performed.